2011
DOI: 10.1016/j.ejphar.2011.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic interactions between MDMA and concomitants in MDMA tablets on extracellular dopamine and serotonin in the rat brain

Abstract: Baseline levels of dopamine and 5-HT in the striatum were 16.5±7.7 and 3.5±1.7 nM (mean ± standard deviation), respectively. After a single administration of MDMA (10 mg/kg, i.p.), a dramatic increase in extracellular dopamine (C max : 36.1-fold vs. baseline) and 5-HT levels (C max : 9.3-fold vs. baseline) was observed. When rats were co-administered with methamphetamine (1, 5 or 10 mg/kg) with MDMA, the dopamine levels induced by MDMA increased in a methamphetamine-dose-dependent manner (C max : 2.5-, 3.5-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…These findings coincide with a previous report of bidirectional effects on the level of anxiety recorded in mice that had been stressed and treated with distinct doses of buspirone, a partial 5-HT1A agonist (Briones-Aranda et al, 2002). This evidence indicates the importance of external factors in the regulation of specific behaviors as ketamine treatment (Ikeda et al, 2011) and stress (Briones et al, 2015) increase the concentration of brain DA and 5-HT, which in turn could influence the actions of nonselective serotonergic agents.…”
Section: Discussionsupporting
confidence: 90%
“…These findings coincide with a previous report of bidirectional effects on the level of anxiety recorded in mice that had been stressed and treated with distinct doses of buspirone, a partial 5-HT1A agonist (Briones-Aranda et al, 2002). This evidence indicates the importance of external factors in the regulation of specific behaviors as ketamine treatment (Ikeda et al, 2011) and stress (Briones et al, 2015) increase the concentration of brain DA and 5-HT, which in turn could influence the actions of nonselective serotonergic agents.…”
Section: Discussionsupporting
confidence: 90%
“…These interactions result in a net increase of neurotransmitter release from the presynaptic terminal (DA or norepinephrine). Multiple brain studies using microdialysis methods and studies with transporter knockout mice have subsequently confirmed this event (see, for example, [41][42][43][44][45]. These analyses indicated micromolar concentrations of DA and 5-hydroxytryptamine (5-HT) can be achieved in extracellular space.…”
Section: Pharmacodynamicsmentioning
confidence: 81%
“…Previously, we showed that i.p. methamphetamine (10 mg/kg) and 3,4-methylenedioxymethamphetamine (MDMA) (10 mg/ kg) increased dopamine concentration in the striatum of rats up to 6000 and 1620 % from baseline, respectively [14,15]. In addition, these drugs both increased serotonin concentrations in the striatum by up to 1300 %.…”
Section: Resultsmentioning
confidence: 99%
“…Forensic Toxicol HPLC-ECD conditions for determination of dopamine and serotonin HPLC-ECD conditions for determination of dopamine and serotonin concentrations were similar to those described in previous reports [14,15]. Briefly, the HPLC system was an HTEC-500 (Eicom) equipped with an ECD.…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation